2013
DOI: 10.1017/s1047951113000851
|View full text |Cite
|
Sign up to set email alerts
|

Glial fibrillary acidic protein in children with congenital heart disease undergoing cardiopulmonary bypass

Abstract: There are significant increases in glial fibrillary acidic protein levels in children undergoing cardiopulmonary bypass for repair of congenital heart disease. The highest values were seen during the re-warming phase. Elevations are significantly associated with younger age, bypass and cross-clamp times, and temperature nadir. Owing to the fact that glial fibrillary acidic protein is the most brain-specific biomarker identified to date, it may act as a rapid diagnostic marker of brain injury during cardiac sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…8 Elevations in levels of GFAP are detectable within 30 minutes of CPB and are not affected by ultrafiltration. 19 GFAP levels have been associated with neurological disability in adults with traumatic brain injury and those surviving cardiac arrest. [9][10][11] In the pediatric population, circulating GFAP has been shown to be a significant predictor of neurologic injury and hospital survival in children receiving extracorporeal membrane oxygenation, of abnormal magnetic resonance imaging and functional outcomes at discharge in neonates with birth-related hypoxic ischemic encephalopathy, and of periventricular white matter injury on 6-week head ultrasound imaging in premature infants.…”
Section: Blood-based Biomarkers and Neurologic Injurymentioning
confidence: 99%
“…8 Elevations in levels of GFAP are detectable within 30 minutes of CPB and are not affected by ultrafiltration. 19 GFAP levels have been associated with neurological disability in adults with traumatic brain injury and those surviving cardiac arrest. [9][10][11] In the pediatric population, circulating GFAP has been shown to be a significant predictor of neurologic injury and hospital survival in children receiving extracorporeal membrane oxygenation, of abnormal magnetic resonance imaging and functional outcomes at discharge in neonates with birth-related hypoxic ischemic encephalopathy, and of periventricular white matter injury on 6-week head ultrasound imaging in premature infants.…”
Section: Blood-based Biomarkers and Neurologic Injurymentioning
confidence: 99%
“…(20, 34) In a prior study in pediatric patients undergoing congenital heart surgery (median age, 0.67 years; range, 0.005-17.2 years), our group has reported that plasma GFAP levels were elevated during and after CPB in 70% of cases, peaking during the rewarming phase (p=0.0001). (35) Elevation of plasma GFAP levels are associated with the extent of brain injury in adults with acute stroke and pediatric patients with hypoxic ischemic injury. (22, 27) Detection of plasma GFAP, thus may allow for the early identificatoin of brain injury in a variety of settings.…”
Section: Commentmentioning
confidence: 99%
“…[3][4][5][6][7][8] It is released from glial cells within the central nervous system as a result of cell necrosis. 9 According to Brunetti et al, 10 an ideal biomarker for brain injury is specific to brain tissue and is released into the bloodstream immediately after neurological injury and accurately reflects the location and degree of injury. As the glial fibrillary acidic protein is released into the blood after astrocyte death, it is a suitable biomarker to predict neonatal brain injury.…”
Section: Hd Is the Most Common Congenital Lesion Inmentioning
confidence: 99%
“…As the glial fibrillary acidic protein is released into the blood after astrocyte death, it is a suitable biomarker to predict neonatal brain injury. 9 Glial fibrillary acidic protein has been previously utilised as a diagnostic and prognostic tool in both children and adults; it has been shown to correspond with abnormal brain imaging in neonates, 10 and to predict neurodevelopmental outcomes in neonates with hypoxic ischaemic encephalopathy, prematurity-related intracranial haemorrhage, extracorporeal membrane oxygenation, and cardiopulmonary bypass during repair of neonatal CHD. 8,10 The aim of this study was to determine whether there is a difference in serum glial fibrillary acidic protein levels at birth and the immediate postnatal period between neonates with major CHD and two groups of controls: neonates with hypoxic ischaemic encephalopathy serving as positive controls, and neonates without brain injury serving as negative controls.…”
Section: Hd Is the Most Common Congenital Lesion Inmentioning
confidence: 99%
See 1 more Smart Citation